Influence Analysis of Sprocket Tooth Thickness Effect on Natural Frequency of Mining Scraper Conveyor Chain Drive System - Wang Cunfei (Jixie chuandong)
In order to improve the wear problem of sprockets caused by vibration in the process of mining scraper conveyor operation, the Ansys finite element software is used to analyze the sprocket with different tooth thicknesses respectively. Through the comprehensive analysis of the results, the relationship curve between the sprocket natural frequency and tooth thickness, and the relationship curve between the maximum deformation and tooth thickness are obtained. The results show that for 48 mm×152 mm medium double chain sprockets, the service condition of the sprocket and the size of the supporting scraper should be comprehensively analyzed, and the design parameter with the tooth thickness of 87 mm should be selected, so that the sprocket could have higher natural frequency and smaller corresponding maximum deformation, which can ensure the transmission performance of the ring chain and sprockets. The special points in the analysis results are analyzed to identify special cases that should be avoided for the sprocket mode. When the excitation outside the sprocket cannot be changed, the tooth thickness parameter of 97 mm shall be avoided to prevent excessive deformation of the tooth. The analysis results provide a theoretical basis for the design optimization and manufacturing of the chain drive system of the scraper conveyor used in mining.